2020
DOI: 10.1109/tip.2020.2981922
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Image Understanding in Poor Visibility Environments: A Collective Benchmark Study

Abstract: Existing enhancement methods are empirically expected to help the high-level end computer vision task: however, that is observed to not always be the case in practice. We focus on object or face detection in poor visibility enhancements caused by bad weathers (haze, rain) and low light conditions. To provide a more thorough examination and fair comparison, we introduce three benchmark sets collected in real-world hazy, rainy, and lowlight conditions, respectively, with annotated objects/faces. We launched the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 168 publications
(76 citation statements)
references
References 163 publications
0
64
0
1
Order By: Relevance
“…As pointed out by a plenty of recent works (Wang et al 2016;Liu et al , 2019Liu et al , 2020Scheirer et al 2020;Yang et al 2020;Hahner et al 2019), the performance of high-level computer vision tasks, such as object detection and recognition, will deteriorate in the presence of various sensory and environmental degradation. In particular, Sakaridis et al (2018) studied the effect of image dehazing on semantic segmentation by a synthesized Foggy Cityscapes dataset with 20,550 images.…”
Section: Task-driven Evaluation Setsmentioning
confidence: 99%
“…As pointed out by a plenty of recent works (Wang et al 2016;Liu et al , 2019Liu et al , 2020Scheirer et al 2020;Yang et al 2020;Hahner et al 2019), the performance of high-level computer vision tasks, such as object detection and recognition, will deteriorate in the presence of various sensory and environmental degradation. In particular, Sakaridis et al (2018) studied the effect of image dehazing on semantic segmentation by a synthesized Foggy Cityscapes dataset with 20,550 images.…”
Section: Task-driven Evaluation Setsmentioning
confidence: 99%
“…UAV can also be difficult to detect due to poor visibility in adverse weather conditions, poor lighting, low-quality cameras (on other UAV) and buildings with a similar colour profile. Yang et al [53] survey methods to improve visibility for detection, including de-hazing, de-raining and lowlight enhancement. These methods improve detection results on well-researched objects such as faces, pedestrians and vehicles, but it is unclear whether they transfer to UAV.…”
Section: Object Detectionmentioning
confidence: 99%
“…The results demonstrated that the former methods favored human perception, whereas the latter methods favored numerical metrics. Recently, Yang et al [7] launched a challenge to evoke discussions and explorations regarding exploiting low-level image processing techniques in high-level vision tasks. The results were similar to those displayed by Pei et al [5], signifying large room for development.…”
Section: Introductionmentioning
confidence: 99%